Билингвална интерференция в крайния български Северозапад - Marinov Vladislav (Zenodo, 2008)
The book contains an introduction, two chapters and 4 attachments. The introduction deals with the definition of the object , goals , tasks and methods ofthe research. The object of this sociolinguistic work is the Bulgarian languagesituation in the endmost north-western region of Bulgaria, taking into account theresults of Vlach influence. This problem is crucial and is being reviewed by Bulgarianlinguistics for the first time. The idiolect material was gathered from five villages inthe Municipality of Bregovo.The sociolinguistic methods were the most appropriate to follow, becausethe local residents are bilingual, i.e. in an unofficial environment they use formationsof more than one language (in this particular case – Bulgarian language andVlach dialect). The language situation (LS) in a particular area is a result of the interactionbetween the subsystems of one language or several language formations. Themonolingual LS consists of an a-norm (an urban colloquial literary norm); b-norm (urbanized territorial dialects called mesolects) and c-norm (territorial dialects thathave been only slightly urbanized). In terms of Bulgarian speech used by theresidents of the Municipality of Bregovo, the a-norm is a colloquial literary norm with a few Vlach elements , the b-norm is a West Bulgarian mesolectic norm with Vlach elements and the c-norm is an everyday life colloquial norm with significant number of Vlach elements . All three components of the Bulgarian colloquialspeech in the endmost north-western region are influenced by the Vlach dialectand could be distinguished by their degree of interference .